Driven by fandom: how fan motivation shapes K-pop concert experiences in Malaysia - Abdul Razak, Rayna; Saad, Mazni (IIUM Press, 2026)
K-pop concert tourism has grown rapidly in Malaysia, yet the psychological mechanisms shaping fans’ concert experiences remain insufficiently understood. Hence, this study examines the influence of fan motivation on the fan experience in K-pop concert tourism in Malaysia, specifically whether it significantly affects the experience. Following the Stimulus Organism Response (S O R) framework, fan motivation is theorised as an inner psychological condition that influences the experiential reactions of fans attending concerts. The survey was a quantitative, cross-sectional study of 298 K-pop concert attendees in Malaysia. Analysis was performed in SPSS, and reliability testing and simple linear regression were used to examine the relationship between fan motivation (independent variable) and fan experience (dependent variable). The results show a strong, positive correlation between the variables (R = 0.707), and fan motivation accounts for 49.9% of the variance in fan experience (R² = 0.499). Regression findings also confirm a strong positive influence of fan motivation on fan experience (B = 1.033, p < 0.001). It concludes that fan motivation is a central factor in shaping the concert experience and offers guidance on maximising K-pop concert tourism in Malaysia